Excessive Treadmill Training Enhances Brain-Specific MicroRNA-34a in the Mouse Hippocampus - Xu, Lin; Zheng, Yi Li; Yin, Xin; Xu, Sheng Jia; Tian, Dong; Zhang, Chen Yu; Wang, Sen; Ma, Ji Zheng (Frontiers in Molecular Neuroscience, 2020)
Background: An imbalance between total training load and total recovery may cause overtraining. The purpose of the present study was to verify the effects of overtraining on the expression of brain derived neuro¬trophic factor (BDNF), its receptor tropomyosin receptor kinase B (TrkB) and p75 and the dynamic expression patterns of brain-specific miR-34a and miR-124 or inflammation-related miR-21 and miR-132 in the mouse hippocampus. Method: 8 weeks old C57BL/6J mice were randomly assigned to the control (CON), normal training (NT) and overtraining (OT) groups. An 8-week OT training protocol was applied to evaluate the phenotype of mice endurance (incremental load test) and cognitive capacity (Morris water maze test). We used qRT-PCR and immunoblotting to detect changes in the molecular level of hippocampal samples. Result: Compared with the CON, both NT and OT decreased body weight after 8-week training. After 8-week of training, NT increased the exhaustion velocity (EV) while the EV of OT was lower than NT. Mice in NT decreased the escape latency than CON. The percentage of time spent in the probe quadrant and the number of crossing platform times in NT were higher than CON and OT. The BDNF, p75 and TrkB mRNA levels were increased in NT than CON, only the p75 mRNA was increased in OT. The NT exhibited increased protein levels of BDNF and TrkB compared to CON. The protein expression of BDNF was decreased in OT than NT and CON. The protein level of p75 in the OT was higher than in NT and CON. In addition, the phosphorylation level of TrkB in OT was higher than CON and NT. Only miR-34a level was increased in the OT. Moreover, the expression of miR-34a was found to be negatively correlated with the expression of BDNF, and the increase in miR-34a level was accompanied by a decrease in performance. Conclusion: In summary, the training-evoked increase in the BDNF level may help to improve performance, whereas this conditioning is lost after OT. Moreover, miR-34a potentially mediated changes in the expression of BDNF and may reflect the decrease in performance after OT.